ABREVIASI BAHASA PRANCIS PADA MEDIA SOSIAL TWITTER: SUATU KAJIAN MORFOLOGI - Pratiwi, Widianti Eka; Sofyan, Agus Nero (Universitas Hasanuddin, 2020)
ABSTRACTThis research has a purpose to describe a morphological process called abbreviation. Abbreviation is a shortened form of a written word or phrase used in place of the whole word or phrase. This research uses descriptive qualitative method. The data are tweets in French which were taken on November 10 from Twitter. Overall, from the tweets those were found, there are twenty tweets which contain some words in abbreviated form. The result shows that there are five kinds of abbreviations that exist in those forty tweets, there are apocope, aphérèse, syncope, siglè, and acronyme. The most used abbreviation form is apocope which can be found in 14 tweets, meanwhile the least used one is aphérèse which is available in 4 of forty tweets.